Interaction between visual and verbal modes in the subtitling of the anime movie Your Name / Xu Zhiyi - Xu , Zhiyi (2022)
The purpose of this Audio Visual Translation (AVT) study is to investigate the interactions between the visual and verbal modes, and how the visual mode supports the verbal mode to produce the representational meanings conveyed in the Mandarin translation of the Japanese anime movie, ‘Your Name’. Chen’s (2019) theoretical framework is adopted to guide the investigation on the relationship between three dimensions that is, the Representamen (i.e., verbal mode), Object (i.e., visual mode), and Interpretant (i.e., subtitling). The rationale for the adoption of Chen’s framework is that it allows the study to go beyond technical constraints and cultural gaps which have been commonly discussed in past studies. The study probes into Japanese-Mandarin AVT as there has been less attention paid to East Asian languages. The findings of this study which are based on 89 samples reveal that the verbal mode is supported by the visual mode to fill cultural gaps, maintain narrative flow, avoid redundancy, overcome technical constraints and linguistic differences in subtitling. The interactions between the visual and verbal modes in the movie are found to have undergone explication (15 %), replacement (38 %), generalisation (1 %), addition (43 %), and deletion (7 %), and up to two interactions are observable in one sample. Moreover, Mandarin subtitles in the movie contained either less or more information in comparison with Japanese verbal messages while the essential meaning remained intact. However, there were also instances where the essential meaning in Japanese was sometimes affected in the Mandarin subtitles with the narrative flow being disrupted. The study has highlighted some of the subtitling strategies used when translating from Japanese to Mandarin and the interaction between visual and verbal modes, as well as how the interaction influences subtitling. As this study was only conducted at the representational meaning level, the analytical unit in the visual mode focused only on the shot. It is hoped that studies in the future will view the interaction between the visual and verbal modes on subtitling at the scene and sequence levels.